A8.12 Small Ubiquitin Related Modifier-1 (SUMO-1) Regulates Osteoclastogenesis. (25th February 2013) - Frank, Svetlana; Umlauf, Daniel; Hillmann, Anja; A Jänne, Olli; Pap, Thomas
Abstract : Background and Objectives: Rheumatoid arthritis (RA) is a common autoimmune disease characterised by the hyperplastic transformation of synovium, its infiltration with different inflammatory cells and by stimulation of bone resorption through osteoclast activation leading to joint destruction. Posttranslational modification of proteins by SUMO has been shown for a number of target molecules including transcription factors and is involved in a variety of cellular processes, including protein localisation, transcriptional regulation, protein stability, cell survival and death. Previously, we have shown that the increased expression of SUMO-1 contributes to the inflammatory response in RA. Here, we investigated the role of SUMO-1 in osteoclastogenesis and studied the skeletal phenotype of SUMO-1 -/- mice under physiological conditions. Materials and Methods: For all in vitro experiments, bone marrow macrophages were isolated from SUMO-1 -/- mice and wild type (WT) controls and were cultured in the presence of macrophage colony-stimulating factor and receptor activator of nuclear factor k-B ligand. Osteoclast differentiation was verified by tartrate-resistant acid phosphatase (TRAP) staining. Using real time PCR mRNA levels of DC-STAMP and Cathepsin K were analysed. Proliferation of preosteoclasts was determined using CyQuant proliferation assay. Osteoclast resorption capacity was analysed using a calcium phosphate bone resorption assay. The skeletal phenotype of 8-week old mice was investigated by µCT-analysis of trabecular bone in the lumbar spine and femora. The vertebral bodies L5 from each animal were dehydrated and embedded nondecalcified into methylmetacrylate for sectioning. Sections were stained using van Kossa and for TRAP activity. Results: In PCR analyses, we found decreased expression of DC-STAMP and Cathepsin K in SUMO-1 -/- mice compared to wt mice during osteoclast differentiation. Proliferation of preosteoclasts was not affected by loss of SUMO-1. In osteoclast formation assays, the loss of SUMO-1 was associated with impaired osteoclast differentiation and with impaired bone resorption capacity. In addition, histological analyses revealed a reduced number of osteoclasts in SUMO-1 -/- mice. At 8-weeks old, SUMO-1 -/- mice had a 20% higher trabecular bone volume fraction compared with wt mice. Moreover, trabecular thickness was higher and trabecular separation was lower in SUMO-1 -/- mice. Conclusions: In our study, we found that SUMO-1 -/- mice have high bone mass owing to a decrease in number, size and function of osteoclasts. Furthermore, osteoclast markers contributing to osteoclast fusion and to osteoclast resorption capacity were decreased. These data suggest that SUMO-1 is involved predominantly in the regulation of bone mass by osteoclast formation and activity, and therefore may be an interesting target for treating diseases associated with bone loss.